Pemanfaatan Candi Sukuh Sebagai Sumber Belajar Sejarah Bagi Mahasiswa Tadris IPS IAIN Kudus - Ainun Wahayuningtiyas; Destina Marta Fiani; Dany Miftah M. Nur (FKIP, Universitas Palangka Raya, 2023)
Learning resources are things that educators use to facilitate students in the learning process. Sources of learning are not only from books, but historical objects and sites around us can also be used as learning resources. So far, there are still many who think that the relics of historical sites only function as evidence that there was a relic in the past. Even though the utilization of heritage sites as a source of learning is an important innovation and must be carried out, because heritage sites can provide a more actual description of a phenomenon to students. The purpose of this study is to examine the history of Sukuh Temple and the extent to which the effectiveness of using the Sukuh Temple site as a learning resource in Indonesian History courses. Research using descriptive qualitative research methods. Data collection techniques used in this study are interview techniques, observation and literature study. The results showed that the Sukuh Temple, which is located in the Karanganyar area, has compatibility with the lecture material in the curriculum of the Social Sciences Tadris Study Program at the Kudus State Islamic Institute, namely in the Indonesian History course. And there is one basis for implementing the curriculum that supports the utilization of the Sukuh Temple site in Karanganyar as a learning resource